Covid-19: Disadvantages Of Online Learning Towards Visual Arts Practiced-based Nature - Mohd Fauzi Sedon; Che Zalina Zulkifli; Mohd Zahuri Khairani; Abu Bakar Sabran; Abdul Aziz Zalay (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: This paper discusses the disadvantages of online learning in the context of studio practice -based that focuses on practical skills. Discussions are made by looking at various angles of teaching and learning toward the online method and its implications for the field of Visual Arts. Among the aspects discussed are social isolation, limited feedback, focus on theory rather on practice, lack of flexibility, and lack of transformational power. In general, online learning can only serve as a supporting method to the field of Visual Arts that focuses on the construction of practical skills, where conventional learning method which is characterized by practice-based learning is more appropriate and effective. Design/methodology/approach: Review approach. Findings: The best practices for online learning courses are still evolving and are much more difficult to implement especially in terms of learning methods that would be suitable and effective for all areas. Direct training, standard methods, approaches and processes through practice-based are the best practices and are much more established, well understood and more effective for teaching and learning in Visual Arts. Practical implications: Developing a truly effective online learning course requires time, money, and a huge amount of expertise. Good online learning courses involve multimedia, specialized web development, technical support, and strong user interaction design. If done incorrectly, it will disrupt and negatively impact the learning process because of the lack of time concentrations and space limitations. Originality/value: This paper is original. Paper type: This paper can be categorized as a viewpoint